A versatile strategy for preimplantation genetic diagnosis of haemophilia A based on F8-gene sequencing - Sánchez-García, Jorge F.; Gallardo, Dominique; Navarro, Joaquima; Márquez, Carmen; Gris, Josep Maria; Sánchez, Maria Angeles; Altisent, Carme; Vidal, Francisco (Thrombosis and Haemostasis, 2006)
Preimplantation genetic diagnosis (PGD) of hemophilia A (HA) and other X-linked diseases through sex selection implies that male embryos will be systematically discarded, even though 50% are unaffected. The objective of the present work was to develop a PGD protocol for direct mutation identification that could be applied to first polar bodies (1PBs) in several HA clinical cases. Single buccal cells from controls and patients, and 1PBs were subjected to primer extension preamplification (PEP) PCR followed by amplification of F8 gene coding and intronic flanking regions, and direct sequencing. Moreover, multiplex fluorescent amplification of four short tandem repeats was adapted to a single cell preamplification in order to rule out contamination and allele drop-out, and for confirmatory indirect diagnosis. A couple at risk of HA transmission, with a familial mutation characterized as a 41-bp duplication in exon 14 of the F8 gene, was selected for the first clinical study. After optimizing the protocol, the complete F8 gene coding sequence was obtained from single cells to demonstrate the sensitivity of our methodology although in any clinical case only the relevant region, not the whole gene, must be amplified. The woman enrolled in the first clinical case has completed the first in-vitro fertilization cycle, and seven oocytes were analyzed with concordant results by both linkage analysis and direct sequencing method. Only one oocyte, among those diagnosed as mutation free, developed to embryo at day 3. It was transferred but pregnancy was not achieved. This PGD procedure enables non-affected and noncarrier embryo selection in families with any point or smallrange mutation in the F8 gene, without the need for further custom-made modifications.
Keywords: ADO; STR; haemophilia